Prior consultation to indigenous peoples - Mazariegos Rodas, Mónica (EUNOMÍA. Revista en Cultura de la Legalidad, 2016)
The right of indigenous peoples to free, prior and informed consultation in decisions that affect them becomes crucial in Latin America in the current neoliberal model of development’s extractivist phase. Despite constituted as a channel to promote indigenous bottom-up participation, consultation is imbued with a series of profound contradictions, linked at the time of its origin and development in the nineties: the rise of indigenous rights parallel to the rise of global neoliberalism. The legitimacy of consultation, that is, the binding effect of its results, depends on a clever use of law from a counter-hegemonic point of view. doi: http://dx.doi.org/10.20318/eunomia.2016.3289